Charity sector e Chiesa d’Inghilterra (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Lo status di charity - 2. L’amministrazione del patrimonio nella Comunione anglicana e nella Chiesa d’Inghilterra - 3. La promozione della religione nelle decisioni della Charity Commission - 4. Un possibile contributo all’attuazione della riforma del terzo settore.Charity sector and Church of EnglandABSTRACT: The undertstanding signed on 30 july 2019 between the Italian Republic and Association “Church of England”, representing in Italy the Anglican Confession Church of England, renewed the doctrinal debate on ecclesiastical entities and their location in the non profit universe, organically revised by legislative Decree n. 117/2017. In particular, art. 8, third paragraph, of the agreement in question allows the recognition in Italy of ecclesiastical entities that carry out overseas a "prevalent religion and cult activity", for the implementation of which the use of trust is widespread. It’s, therefore, essential, in order to understand the systematic consequences of this choice of undertstanding, to define the characteristics of the third sector in the British legal system, showing particolar attention to the heterogeneous modes of attribution of charitable status, to the regulatory and taxes linked to it and, even more, the concept of advancement of religion as elaborated by the decision of the Charity Commission and, in the review, the High Court. For the same purpose it’s indispensabile to begin the study of the administration of ecclesastical goods in the Church of England and in the Anglican Communion, together with the principles on which it is inspired.